Psychological Adjustment of First-Year Students at Boarding College X in Semarang - Eka Susanti; Mulya Virgonita I. Winta; Erwin Erlangga (CV. Creative Tugu Pena, 2025)
The transition to college is a very challenging phase for new students, especially for students in boarding schools where academic and social demands occur simultaneously. This study aims to obtain an overview of the adjustment process of new students, identify the most challenging dimensions of adjustment, and determine the factors that support new students' adjustment efforts. The study was conducted using a descriptive qualitative method on four first-year students at Semarang X Boarding School (MWM, BJP, NA, and BS). Data were obtained through in-depth interviews and observations, then the data were analyzed using Interpretative Phenomenological Analysis (IPA). The results of the study indicate that the four participants were able to adjust well. The adjustments that were perceived as the most challenging were academic adjustment. Support from parents, friends, and caregivers, involvement in campus activities, and time management skills were supporting factors for the success of the students' adjustment process. The results of this study strengthen previous studies on the importance of social support and the role of institutions in the adjustment process of new students and provide recommendations for the development of new student orientation programs in boarding schools.